Hybridized triboelectric nanogenerators for simultaneously scavenging droplet and wind energies - Chaosheng Hu; Chengmin Bao; Yang Liu; Yingzhan Yan; Yingzhan Yan; Yanan Bai; Qian Xu; Qian Xu (Frontiers in Chemistry)
Triboelectric nanogenerators (TENGs) have attracted great attention due to the simple manufacturing process, low cost, and diverse forms of energy harvesting. However, the energy collected by individual TENG is relatively limited, making it necessary to develop new method to enhance the energy harvesting capability of TENG. Here, we design a hybridized TENG that integrates a droplet-driven TENG and a wind-driven TENG, which exhibits excellent electrical performance. Under the simulated environment of medium rain with medium breeze, the hybridized TENG generates an output voltage of 95.10 V, a maximum average power of 18.15 μW, an energy of 181.54 μJ in 10 s, and charges a 1 μF capacitor to 43.29 V in 120 s. This work enables the harvesting of dispersed wind and droplet energy from the environment, providing new ideas and possibilities for online monitoring in remote areas and the construction of Internet of Things systems.